(untitled) (RT. A Journal on Research Policy and Evaluation, 2017)
The Social Science Centre, Lincoln (SSC), is a co-operative organising free higher education in the city of Lincoln, England. It was formed in 2011 by a group of academics and students in response to the massive rise in student fees, from £3000 to £9000, along with other other government policies that saw the increasing neo-liberalisation of English universities. In this essay we chart the history of the SSC and what it has been like to be a member of this co-operative; but we also want to express another aspect of the centre which we have not written about: the existence of the SSC as an intellectual idea and how the idea has spread and been developed through written publications by members of the centre and by research on the centre by other non-members: students, academics and journalists. At the end of the essay we will show the most up to date manifestation of the idea, the plans to create a co-operative university with degree awarding powers where those involved, students and academics, can make a living as part of an independent enterprise ran and owned by its members for their benefit and the benefit of their community and society.